Potensi Wisata Tradisi Syawalan di Makam Gunung Jati Cirebon - Afghoni, Afghoni; Busro, Busro (Politeknik Pariwisata NHI Bandung, 2017)
The purpose of this study is to examine the potential of Syawalan tourism in the Tomb of Sunan Gunung Jati tourist attraction in the city of Cirebon. This type of research is qualitative research, data collection methods are observation, interviews, library research, and documentation. Source of data in this study are primary data that is obtained through interviews and observations in the field, and secondary data obtained by literature study. Data analysis in this research is descriptive qualitative data analysis. The results found that the tradition of Syawalan in the Tomb of Sunan Gunung Jati has the potential to become one of the leading tourism destinations in Cirebon. The tomb of Sunan Gunung Jati is the main attraction for pilgrims. The tomb of Sunan Gunung Jati becomes the center of Iwalan tradition activities, namely pilgrimage activities. The existence of supporting facilities has also become an advantage, such as inter-city-inter-provincial bus terminals, good road conditions. Parking facilities and restrooms are also almost available in several places so that it supports the comfort of visitors. Based on these results, the local government and the private sector can work together in developing the tradition of syawalan to be the leading tourism city of Cirebon. In addition to the management of tourist attractions can provide education to visitors to always maintain the cleanliness of the places visited.